Deregulation, integration and market structure in European banking - Jordi Gual (EIB Papers, 1999)
This paper discusses the impact of deregulation and market integration policies on the structure of European banking markets. The paper argues that whether European integration will lead to an increased exploitation of scale advantages, or not, will depend on the extent to which competition in banking is based on fixed or variable costs. If competition focuses on variable costs, concentration will diminish with market enlargement when we control for the pro-concentration effect triggered by the deregulation process. Alternatively, when competition focuses on expenses unrelated to the level of intermediation, concentration will not tend to decline as the size of the market grows. This is due to the compensating effect of increased competition in fixed costs such as brand image or electronic banking. I propose a simple test using aggregate data to provide an empirical assessment of the dominant form of competition. The application of this procedure to data for eleven EU countries during the period from 1981 to 1995 yields parameter estimates which indicate that over the period of analysis, competition in Europe tends to be predominantly based on variable costs.
Keywords: 330; Bankenpolitik; Deregulierung; Marktstruktur; Wettbewerb; EU-Staaten